PTH-041 Definitive management of a very rare cause of significant acute upper gastrointestinal bleeding: gastric lipoma resected by hybrid endoscopic submucosal dissection. (17th June 2017) - Koukias, N; Murino, A; Telese, A; Johnson, G; Power, N; Luong, TV; Murray, CD; Despott, EJ
Abstract : Introduction: Gastric lipomas are rare, benign, slow-growing subepithelial tumours. Most lipomas remain asymptomatic and are detected incidentally at endoscopy. Large lipomas however, may very rarely cause significant upper gastrointestinal (GI) bleeding and warrant removal. For the management of large gastric lipomas, laparoscopic excision may be required but endoscopic techniques such as endoscopic submucosal dissection (ESD) and unroofing are also described. This endoscopic video case highlights this rare cause of upper GI bleeding and its definitive management by hybrid ESD. Method: A 66 year old man presented with melaena, pallor and fatigue. On admission, his haemoglobin level was 89 g/L. The patient underwent an upper gastrointestinal (GI) endoscopy during which a 3 cm ulcerated submucosal lesion was identified at the greater curvature. An endoscopic clip and Hemospray(R) were applied and haemostasis was achieved. Computed tomography imaging revealed an ovoid (fat density) lesion measuring 25 × 15 mm consistent with a lipoma. Endoscopic ultrasound assessment of the lesion was subsequently performed which showed the presence of an homogenous and slightly hyperechoic lesion 25 × 15 mm arising from the hyperechoic submucosal layer. A 22g needle was used to obtain core biopsies but unfortunately the sample was inadequate for diagnostic assessment. Results: Endoscopic management of the lesion was agreed and the lesion was successfully resected by hybrid ESD. No immediate or delayed adverse events were encountered. Histopathology confirmed the diagnosis of submucosal gastric lipoma which was completely excised. On repeat endoscopy three months post-procedure, a well healed scar was seen at the site of excision. Conclusion: Our video case highlights the role of hybrid ESD in the minimally invasive and definitive management of this rare submucosal cause of upper GI bleeding. References: . Lee KJ, Kim GH, Park DY, et al. Endoscopic resection of gastrointestinal lipomas: a single-centre experience. Surgical endoscopy2014; 28: 185–192 . Matsushita M, Fukata N, Okazaki K. Endoscopic removal of large gastric lipomas: en bloc resection with submucosal dissection or partial resection with unroofing technique?Dig Endosc. 2013Mar;25(2):211–2. doi: 10.1111/den.12011. Epub 2012 Dec 17. Disclosure of Interest: None Declared